2001
DOI: 10.1590/s0100-40422001000100003
|View full text |Cite
|
Sign up to set email alerts
|

Análise dos álcoois, ésteres e compostos carbonílicos em amostras de óleo fúsel

Abstract: Recebido em 19/8/99; aceito em 29/8/00 ANALYSIS OF THE ALCOHOLS, ESTERS AND CARBONYL COMPOUNDS IN FUSEL OIL SAMPLES. Analysis of alcohols, esters and carbonyl compounds were performed using HRGC and HPLC techniques in samples of fusel oils from three different Brazilian alcohol distilleries. High content of isoamyl alcohol (390 g.L -1 ), isobutyl alcohol (158 g.L -1 ), ethyl alcohol (28,4 g.L -1 ), methyl alcohol (16,6 g.L -1 ) and n-propyl alcohol (11,9 g.L -1 ) were found. These compounds represent 77 ± 8 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 4 publications
1
11
0
9
Order By: Relevance
“…The injection mode was 1 : 15 and injection volume was 1 mL. 1 H and 13 C NMR analyses were recorded on a Bruker DRX400 Ultra Shield NMR spectrometer, 400 MHz, at 25 C. The solvent used in the experiments was CDCl 3 . FT-IR analyses were performed on a Bruker spectrophotometer, Model Vector 22, KBr pellets.…”
Section: Procedures For the Synthesis Of Alkyl Carbonate From Cholesterolmentioning
confidence: 99%
“…The injection mode was 1 : 15 and injection volume was 1 mL. 1 H and 13 C NMR analyses were recorded on a Bruker DRX400 Ultra Shield NMR spectrometer, 400 MHz, at 25 C. The solvent used in the experiments was CDCl 3 . FT-IR analyses were performed on a Bruker spectrophotometer, Model Vector 22, KBr pellets.…”
Section: Procedures For the Synthesis Of Alkyl Carbonate From Cholesterolmentioning
confidence: 99%
“…Souza & Llistó (1978) reported that fusel oil may also contain hexyl, heptyl and octyl alcohols in small quantities. However, the main constituent of fusel oil is isoamyl alcohol (Vauclair et al 1997;Kuçuk & Ceylan, 1998;Pérez et al 2001;Ceccato-Antonini & Silva, 2002;Azania, 2003, Nascimento et al 2003, which comes from the decomposition of iso-leucine, an amino acid derived from the hydrolysis of proteins in yeast (Codistil, 1978). According to Nascimento et al (2003), isoamyl alcohol has been investigated by chemical industries as a reagent in organic synthesis or as a solvent in the extraction of pharmacological compounds such as esters.…”
Section: General Characteristics Of Fusel Oilmentioning
confidence: 99%
“…The planting of sugarcane, which is costly and consumes considerable amounts of herbicides that may even harm the environment, could benefit from the use of this byproduct. From this standpoint, Pérez et al (2001) thought that the low commercial value of fusel oil coupled with high production volume of crops are factors that should encourage proposals to develop technology to use fusel oil. Consequently, the choice of desiccant herbicides for of sugarcane reform is essential for the selection of both the sugarcane and the species that can be cultivated after eradication of the ratoon.…”
Section: Eradication Of Sugarcane With Application Of Fusel Oil Spraymentioning
confidence: 99%
“…The assignment of environmental loads among the distillery coproducts-ethanol, fusel oil and vinasse in the case of sugarcane, and all these as well as Dried Distillers Grains with Solubles (DDGS) for starchy sources-was based on the (C/H) ratio of those flows, which have been established from typical compositions [41][42][43]. The decision was made due to the energy nature of the systems under analysis and their co-products, which can be quantified from that relation.…”
Section: Scope Definitionmentioning
confidence: 99%